2014
DOI: 10.1515/helia-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Seed Yield and Quality of Sunflower (Helianthus annuus L.) as Influenced by Staggered Sowing and Organic Fertilizer Application in the Humid Tropics

Abstract: Two field experiments were conducted on the Teaching and Research Farm of the Federal University of Agriculture, Abeokuta (7°15′ N, 3°25′ E, altitude 140 m above sea level) in south western Nigeria between June and November, 2012 to evaluate the performance of two sunflower varieties (SAMSUN-3 and Funtua) as affected by different sowing dates and organic fertilizer application. The experiment was laid out in split-split plot design with sowing dates as main plot, organic fertilizer as sub-plot and variety as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Utilization of the optimum fertilizer rate enhances soil physical and chemical properties, minimizes nutrient imbalance, and promotes better crop growth and development. However, reports on optimum rates of organic and inorganic fertilizer for sunflower growth on nutrient deficient soil in many sunflower growing countries such as Egypt [11], India [12], Sudan [13] including southwestern Nigeria [14] are scanty.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of the optimum fertilizer rate enhances soil physical and chemical properties, minimizes nutrient imbalance, and promotes better crop growth and development. However, reports on optimum rates of organic and inorganic fertilizer for sunflower growth on nutrient deficient soil in many sunflower growing countries such as Egypt [11], India [12], Sudan [13] including southwestern Nigeria [14] are scanty.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of AtMYB96 gene has confirmed the drought tolerance in Arabidopsis and its knockout mutant has proved more drought sensitivity than wild type plants ( Seo et al, 2011 ). Transcriptional activation of AtMYB96 under drought-stress and role of wax-biosynthesis has been confirmed later on ( Oshundiya et al, 2014 ). They also reported that wax deposition was increased on Arabidopsis leaves and stem during the activation of myb96-1D mutant.…”
Section: Introductionmentioning
confidence: 84%
“…All the MYB TFs involved in cuticular wax biosynthesis are the members of R2R3-MYB subfamily of TFs. In Arabidopsis, MYB TFs involved in cuticular wax biosynthesis under drought are AtMYB16 , AtMYB30 , AtMYB41 , AtMYB94 , AtMYB96 , AtMYB106 , and AtMYB116 and a TF SlMYB12 has been reported in tomato ( Cominelli et al, 2008 , Seo et al, 2011 , Oshundiya et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant effect of genotypes, with Helio250 and Helio253 (Figure 4) showing lower reductions of 1.37 and 0.67%, respectively, in the oil content of the achenes harvested when compared to those before cultivation, thus demonstrating their adaptation to the culture conditions of the Paraí ba semi-arid region. ISSN 2166-0379 2019 According to Oshundiya et al (2014), oil content in the sunflower achenes can be reduced due to climatic conditions and cultural practices during cultivation, particularly during the phase of achenes filling. It was observed that the genotypes Embrapa122 and BRSG01 were more affected in their oil content, possibly because they suffer more from the cumulative effects of temperature, high luminosity and other environmental variables present in the region.…”
Section: Oil Contentmentioning
confidence: 99%